Motivating Students of SMK Muhammadiyah 1 Palu for Increasing English Language Vocabulary - Mawardin M Said; Ferry Rita; Abdul Waris; H Jamiluddin (Universitas Negeri Surabaya, 2020)
Main issue of this commuity service is Motivating Students. Its objective was Increasing Vocabulary of English Language. Its specific target is SMK Muhammadiyah 1 Palu has students who have more vocabulary so that they can easily understand and express sentences of the EFL (English as a Foreign Language). They can be global students if they can increase vocabulary to express the internatonal language. Commuicative method was used to reach the objective. Formerly they were shy and unconfident in expressing the language vocabulary, but after being motivated to increase the global language vocabulary they then were confident to practice it by interacting with the community service team and have spirits better better than before to increase the vocabulary of English so that they can express the lingua franca words. The team motivated them to increase their English vocabulary practically and accompanied them to apply the practical ways of increasing the EFL vocabulary so that they have been able to express its words. They can be motivated to increase the vocabulary by telling them status and significances of English in Indonesia.Keywords: Motivating, Increasing, English, Language, Vocabulary